INTERVENTIONS OF THE COOPERATIVE, SME, INDUSTRY AND TRADE OFFICE OF MEDAN CITY IN SUPPORTING MSME EMPOWERMENT - Gilbert Parningotan Simatupang (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
One of the efforts in poverty alleviation is to empower micro, small, and medium enterprises (MSMEs). This is stipulated in Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises. The socialization of policies in supporting the empowerment of MSMEs is still not optimal due to the lack of maximum services and special policies issued by the government, especially the Office of Cooperatives, SMEs, Industry and Trade of Medan City. This research aims to see and analyze by conducting diagnosis through interventions given to local governments, especially for the Office of Cooperatives, SMEs, Industry and Trade of Medan City in terms of supporting MSME empowerment. Diagnosis is a simple way to find out the problem which is then carried out the process of solving the problem by means of intervention. As for after the diagnosis, it is expected to provide a change in the way of working that is better than before. The research method used in this research is a qualitative method. This research presents the results of the intervention analysis which can later be considered by policy makers and policy actors so that every policy issued, especially for the empowerment of MSMEs, can be felt by the people of Medan City, especially micro, small and medium enterprises. Therefore, public policy is basically a matter of making decisions on future choices.